BEBERAPA CATATAN ATAS USUL PERUBAHAN KELIMA UUD 1945: Belajar dari Pengalaman Perubahan UUD 1945 Tahun 1999-2002 - Fadjar, Abdul Mukthie (Jurnal Konstitusi, 2011)
The Local Representative Assembly (DPD) in the periode of 2009-2014 states to the public on the proposal of the fifth change of the 1945 Constitution using “a new package” with “the consolidation of democracy and national true identity”. The DPD should learn from experiences of the first up to fourth changes, either procedurally or substantially.